2013
DOI: 10.1253/circj.cj-12-0987
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural Maturation of Human-Induced Pluripotent Stem Cell-Derived Cardiomyocytes in a Long-Term Culture

Abstract: Background:In the short-to mid-term, cardiomyocytes generated from human-induced pluripotent stem cells (hiPSC-CMs) have been reported to be less mature than those of adult hearts. However, the maturation process in a long-term culture remains unknown. Methods and Results:A hiPSC clone generated from a healthy control was differentiated into CMs through embryoid body (EB) formation. The ultrastructural characteristics and gene expressions of spontaneously contracting EBs were analyzed through 1-year of culture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
231
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 262 publications
(248 citation statements)
references
References 34 publications
15
231
0
2
Order By: Relevance
“…Once differentiated, hiPSC-CMs can be kept in culture for several months (Bedada et al 2014;Kamakura et al 2013). During differentiation, hiPSC-CMs rapidly express contractile proteins (Fig.…”
Section: Hipsc-cm Maturationmentioning
confidence: 99%
See 1 more Smart Citation
“…Once differentiated, hiPSC-CMs can be kept in culture for several months (Bedada et al 2014;Kamakura et al 2013). During differentiation, hiPSC-CMs rapidly express contractile proteins (Fig.…”
Section: Hipsc-cm Maturationmentioning
confidence: 99%
“…The β-adrenergic stimulation pathway also undergoes major modifications during the differentiation process (Jung et al 2016). Longer culture times are known to greatly improve the morphology and function of hiPSC-CMs (Kamakura et al 2013;Lundy et al 2013). Lundy et al reported that hiPSC-CM circularity decreases with aging and is accompanied by an increase in myofibril density and organization (Lundy et al 2013).…”
Section: Hipsc-cm Maturationmentioning
confidence: 99%
“…Alternatively, hPSC-derived cardiomyocytes at the current maturity could be studied and the cardiac channels deconstructed such that a mature phenotype could be generated via computer-based modeling (31). A less optimal approach to maturity is to culture for extended periods of time, as 1 year in culture led to myosin and band changes indicative of adult cardiomyocytes (32,33). Thus, there are a multitude of avenues to explore maturing cardiomyocytes should the scientific need arise.…”
Section: Cardiomyocytesmentioning
confidence: 99%
“…Embryoid bodies are three-dimensional aggregates of pluripotent stem cells that undergo differentiation and cell specification into all the three-germ layers including CM in a manner similar to the early embryo [216][217][218][219]. In this technique, small clumps of pluripotent stem cell are dispersed in a suspension culture containing serum media to form spherical aggregates.…”
Section: Embryoid Body Formationmentioning
confidence: 99%
“…Over the years that followed, a series of optimization studies examined the capacity of first generation iPSC lines to differentiate into CM lineages [214,215]. These approaches include Embryoid Body formation (EB) [216][217][218][219] co-culture with stromal layer [220] and direct cytokine-guided differentiation [221].…”
Section: Cardiac Differentiation Of Pluripotent Stem Cells 71 Introdmentioning
confidence: 99%